The Effectiveness of K3LH Social Mobilization Training Against the Understanding of HR Management Karang Taruna Pakalongan Village After the Earthquake Disaster - Muhammad Dzaki Anshori; Yuli Damayanti; Dewi Anggrayni (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The K3LH Social Mobilization Training is a short-term educational activity to provide basic and technical insight regarding the application of K3LH in evacuating and removing debris from buildings damaged and destroyed by earthquakes. The training was conducted in Pakalongan Village, Padaluyu Village, Cianjur Regency. This area is one of the areas affected by the Cianjur earthquake on November 21, 2022. This research was conducted to find out the level of effectiveness of the training for training objects. The approach used in this study was the quantitative method, in which the researcher distributed questionnaires in the form of questionnaires to youth groups in Paduluyu Village who were respondents to the study. The results of this study indicate that K3LH mobilization training has a positive and significant influence on the understanding of Karang Taruna HR management in the work process. In addition, this research also shows that with an understanding of K3LH Mobilization, Youth Organizations in Paduluyu Village also know how to do public speaking as a means of the mobilization process. The recommendation for further research is to examine how the effectiveness of mobilization training in public communication with the people in Paduluyu Village, besides that the researcher also recommends that further research expand the number of respondents in their research.